Pengaruh Kompres Hangat terhadap Penurunan Nyeri Sendi pada Lansia dengan Penyakit Gout Arthritis - Ulfa Hasana; Asniati Asniati; Noviyanti Noviyanti (Jurnal Kebidanan Harapan Ibu Pekalongan, 2022)
Gout is a condition of the end result of purine metabolism that can cause symptoms of unbearable pain, swelling and a burning sensation in the joints. This makes the elderly experience a decrease in the ability to carry out daily activities so that giving warm compresses is needed for the elderly. The purpose of the study was to determine the effect of warm compresses on reducing joint pain in the elderly with gout arthritis at UPT PSTW Khusnul Khotimah Pekanbaru. The research design used was pre experimental designs with the design of ''One Group Pretest and Posttest. The population of all elderly people with gout at UPT PSTW Khusnul Khotimah Pekanbaru is 17 elderly people with a sample of 17 elderly people. The sampling technique is total sampling. The results of the study using statistical tests obtained the value of value = 0.000 < (0.05). It can be concluded that research shows the effect of warm compresses on reducing joint pain in the elderly with Gout Athritis disease at UPT PSTW Khusnul Khotimah Pekanbaru.